Foods elaborated with vegetable by-product effects on blood lipid levels: A systematic review - Yolanda E. Pérez-Beltrán; Francisco J. Blancas-Benítez; Suecia Aranda-Carrillo; Carolina Fregoso- Ultreras; Sofía Chairez-Huerta; Juscelino Tovar; Sonia G. Sáyago-Ayerdi (Food Chemistry Advances)
Vegetable by-products, produced in large quantities worldwide, contain significant amounts of bioactive compounds and fiber, which have been shown to offer health benefits, such as regulating blood lipid levels. Dyslipidemia, a primary target in the clinical metabolic control of susceptible populations, is strongly influenced by diet. Hence, this systematic review aims to present the main findings on the tested effect of consuming vegetable by-products as part of a regular diet on lipid-related alterations in humans and murine models.The PRISMA protocol was followed to carry out this systematic review. The main results are outcomes related to ameliorating dyslipidemia and those significant findings linked to improving health status when consuming the vegetal by-product.About 15,706 articles were identified, but only 19 were considered to fulfill the inclusion criteria established based on the reported data. The acquired information was organized based on the effect of consumption of vegetable by-products tested in murine models and tested in human intervention studies.Findings included in this systematic review indicated that diverse bioactive present in vegetable by-products act as antioxidants, stimulators of biochemical processes such as thermogenesis, and even regulators of gene and microRNA expression, so when incorporated into the usual diet, they can provide a beneficial effect on lipid-metabolic related alterations, at the same time, they contribute to better management of food waste and sustainability.